Study of clinical profile and laboratory markers in early diagnosis of severe dengue in children - Srinivas, Suprith Amblihalli; Pol, Ramesh (International Journal of Contemporary Pediatrics, 2024)
Background: Dengue fever is a mosquito-borne viral disease that presents as asymptomatic or can clinically manifest with symptoms like hemorrhagic fever and shock. Alteration of various other hematological parameters includes leukopenia, thrombocytopenia, hematocrit changes, and liver enzyme alteration. this study aimed to investigate dengue patients’ clinical profiles, laboratory parameters, and outcomes across different severity levels. Methods: This is a prospective hospital-based study of 125 patients conducted at S. Nijalingappa medical college, Bagalkot over 18 months from August 2022 to February 2024. the study included 125 cases with serologically confirmed (NS1ag and/ IgM) between 1 to 14 years and categorized according to WHO classification. Results: Out of 125 patients, 62 and 33 had dengue with and without warning signs, and 30 had severe dengue, 52% of cases had leucopenia, and thrombocytopenia was present in 105 (84%) cases with significantly higher in severity groups. Elevated SGOT 108 (86.4%) and SGPT 72 (57.6%) were commonly seen in disease severity groups. Liver dysfunction was observed in 86.4% of patients. All patients survived and improved with appropriate treatment. Conclusions: This study highlights the importance of clinical and hematological parameters in the early recognition and management of severe dengue cases. Liver dysfunction was common in severe cases. Despite the varying severity, all patients in this cohort had favorable outcomes, emphasizing the effectiveness of proper management strategies.